Population structure, resource potential and diagnostic features of raw materials of Saussurea controversa DC - Parshina, Evgeniya P.; Reshetov, Yaroslav E.; Krasnobaeva, Alina A.; Avdeeva, Elena Yu; Belousov, Mikhail V.; Shurupova, Margarita N. (Вестник Томского государственного университета. Биология)
The life form and the ontogenesis of the perspective medicinal plant Saussurea controversa DC. (Asteraceae) are described. The species is considered as polycentric, perennial, summer-green, herbaceous polycarpic half-rosette plant with rhizome. The aerial part of the plant includes the polycyclic rosette vegetative and elongated generative shoots. In the ontogenesis, four periods and nine ontogenetic states are distinguished. The ontogenetic and vital structures of four  populations were studied in the vicinity of Efremkino village (Republic of Khakassia). Populations are incomplete with accumulation of virginal individuals and predominance of individuals of intermediate and high classes of vitality. Analysis of the distribution and resource research in the population with the highest density and area makes it possible to classify the species as the 3rd category of resource species due the necessity to observe the regime of sustainable use. The diagnostic features of the S. controversa's raw material are the structure of the middle vein of the leaf which includes a large number of vascular-fibrous beams and the abaxial epidermis containing stomata of the anomocytous type and 4 types of trichomes.